Bust of John Steinbeck - Frank Gaughen:::Creator::::::::::::
Photo of a John Steinbeck bust sculpted in 1964 by Joseph Brown. Purchased by a private owner at Sotheby's Auction. Bust is 57cm high, 37cm long, 25cm wide. Base is 8cm high, 30cm long, 23cm wide. The sculpture is inscribed with 'Ad Astra per Alia Porci.' Photograph taken in 2006 by Frank Gaughen. Digital copy only.not in safe